2003
DOI: 10.1099/vir.0.19062-0
|View full text |Cite
|
Sign up to set email alerts
|

The membrane proteins of flaviviruses form ion-permeable pores in the target membrane after fusion: identification of the pores and analysis of their possible role in virus infection

Abstract: Recently, we presented evidence that the E1 fusion protein of the alphavirus Semliki Forest virus forms ion-permeable pores in the target membrane after fusion. We proposed that the homologous fusion proteins of flaviviruses and hepatitis C virus form similar pores. To test this hypothesis for the E fusion protein of flaviviruses, the release of [ Release from certain liposomes was activated even at neutral pH. To identify the generation of individual pores, single cells were investigated with the patchclamp t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The low rate of entry seen at nonphysiological cold temperatures may reflect the impairment of cellular functions that may be required to favor the genome delivery process. Supporting this model of infection is the observation that alphavirus entry into living cells is a leaky process (33)(34)(35), allowing the passage of small molecules and ions through the plasma membrane. In contrast, virus-liposome membrane fusion has been shown to be a nonleaky process (36).…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of entry seen at nonphysiological cold temperatures may reflect the impairment of cellular functions that may be required to favor the genome delivery process. Supporting this model of infection is the observation that alphavirus entry into living cells is a leaky process (33)(34)(35), allowing the passage of small molecules and ions through the plasma membrane. In contrast, virus-liposome membrane fusion has been shown to be a nonleaky process (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, these eVects are much less pronounced than for Alphaviruses with respect to the overall fusion and can only be demonstrated when fusion is slowed down by lowering the temperature (Stiasny et al 2003). Recent data suggested that Flaviviruses could enter their host cells by fusing with the plasma membrane at neutral pH, due to an interaction with a membrane patch of appropriate lipid composition (Koschinski et al 2003). However, increasing in vivo evidence indicates that most Flaviviridae enter their host cells by endocytosis after receptor recognition at the plasma membrane (Stiasny and Heinz 2006).…”
Section: Speciwc Interactions Between Viral Envelope Glycoproteins Anmentioning
confidence: 99%
“…We have previously shown that lanthanide ions block the ion pores generated during entry of alphaviruses at the plasma membrane without interfering with productive infection (Koschinski et al , 2005). As similar ion-permeable pores are generated during entry of the flavivirus West Nile virus (WNV) (Koschinski et al , 2003), we analysed the effect of lanthanide ions on the establishment of a productive infection by flaviviruses. The results of these studies are reported in this paper.…”
Section: Introductionmentioning
confidence: 99%